Comparative research on stability of baicalin and baicalein administrated in monomer and total flavonoid fraction form of Radix scutellariae in biological fluids in vitro - Zhiqiang Feng; Jie Zhou; Xueying Shang; Guojun Kuang; Jian Han; Liping Lu; Lei Zhang (Taylor & Francis Group, 2017)
Context: Baicalin (BL) and baicalein (B) as the major flavonoids of Scutellaria baicalensis Georgi (Lamiaceae) have been investigated intensively, and shown to possess a multitude of pharmacological activities. Objective: This study systematically evaluates the stability of BL and B in monomer and total flavonoid fraction (FSR) form in vitro, and further studies whether the protective measures are effective to make B and BL stable enough to meet the requirement of quantitative analysis in various biological samples. Materials and methods: The stability of BL and B was evaluated by investigating the influence factors such as pH (2.0, 3.0, 4.5, 6.8, 7.4 and 9.0), temperature (4, 25 and 40 °C), antioxidant (vitamin C and Na2SO3) and sunlight. After the protective measures were taken, stability of BL and B in plasma, urine and tissue homogenates was evaluated through post-preparative stability (stored at 4 °C for 24 h), three freeze-thaw cycles stability and long-term stability test (stored in refrigerator at −20 °C for 15 days). In addition, by comparing the degradation parameters of BL and B obtained from the monomer administration group with those of the FSR administration group, drug-drug interaction of coexistent components in FSR on the stability of BL and B was discussed. Results: The degradation of BL and B was both pH- and temperature-dependent with their correlation coefficents for first-order kinetics equation larger than 0.99, and acidic environment (pH 2-4.5), lower temperature (<4 °C) and acidic antioxidant (e.g. vitamin C) were conducive to stabilize B and BL. Furthermore, coexistent components in FSR were proved to have function on inhibiting the degradation of BL and B in our study for the first time, which was characteristic of prolonging their biological half-life (t1/2) significantly, e.g., from 2.89 h to indefinite for BL (pH 6.8, 25 °C), from 2.63 h to 4.48 h for B (pH 6.8, 25 °C) and so on. Antioxidant of Na2SO3 could inhibit the degradation of BL with t1/2 increasing from 1.8 h to 3.5 h, but aggravate the bio-transformation of B with t1/2 decreasing from 0.92 h to 0.29 h. Our research proved that BL monomer, and BL and B in FSR form could be stabilized enough to meet the requirement of biological quantitative analysis under the protection of coexistent components in FSR. Discussion and conclusion: The results obtained indicated that the stability of BL and B was affected not only by its environmental parameters, but also by the coexistent components in the effective total flavonoids fractions.